Reichstagswahlen. Von Hindenburg nach dem Wahlakt. Hinter ihm: Staatssekretär Meissner. Aus: Album 19, no. 64
Reichstagswahlen. Von Hindenburg nach dem Wahlakt. Hinter ihm: Staatssekretär Meissner. Aus: Album 19, no. 64.